PREVALENCE AND ETIOLOGY OF IRON DEFICIENCY ANEMIA BETWEEN 5 MONTHS TO 5 YEARS OF AGE (The Research of Medical Science Review, 2025)
Background: Iron deficiency anemia (IDA) is the most prevalent nutritional deficiency worldwide and a major contributor to pediatric morbidity, particularly in low- and middle-income countries. In early childhood, IDA has profound implications for neurodevelopment, immune competence, and physical growth, which can result in long-term cognitive and functional impairments. In Pakistan, the prevalence of pediatric anemia remains high despite public health efforts, likely due to persistent socioeconomic disparities, suboptimal feeding practices, and poor hygiene and sanitation conditions. Identifying the frequency and key risk factors of IDA in specific local populations is essential to designing effective prevention and management strategies. Objective: The objective of this study was twofold: first, to determine the frequency of iron deficiency anemia in children aged 5 months to 5 years presenting to a tertiary care hospital in Southern Punjab; and second, to evaluate the major etiological factors contributing to IDA in this population, including perinatal history, environmental exposures, dietary habits, and socioeconomic indicators. Methods: A descriptive, cross-sectional study was conducted at the Department of Pediatric Medicine, Bahawalpur Victoria Hospital, over a six-month period from July 2, 2024, to January 1, 2025. A total of 240 children aged 5 to 60 months, presenting with mild illnesses or for routine vaccination, were recruited through consecutive non-probability sampling. Children already on iron supplementation or suffering from chronic infections or systemic illnesses were excluded. Blood samples were analyzed for hemoglobin and serum ferritin levels; IDA was diagnosed based on hemoglobin <10 g/dL and serum ferritin <12 ng/mL. Data on potential etiological factors—such as low birth weight, preterm delivery, family history of anemia, poor hygiene, sanitation status, and feeding practices—were collected through structured interviews and clinical assessments. Data were analyzed using SPSS version 25. Statistical associations were evaluated using Chi-square or Fisher’s exact test, with p ≤ 0.05 considered significant. Results: Out of the 240 children included in the study, iron deficiency anemia was diagnosed in 86 patients, yielding a frequency of 35.83%. The majority of anemic children were between 5 and 36 months of age, with a slight male predominance (male-to-female ratio: 1.3:1). The most prevalent risk factor was low socioeconomic status, identified in 38.37% of anemic cases, followed by unsafe sanitation (36.05%), poor hygiene (30.23%), and the use of cow milk as a primary feed (25.58%). Other notable associations included low birth weight (24.41%), family history of anemia (20.93%), and preterm birth (16.28%). Children with lower body weight (≤5 kg) and shorter symptom duration (≤7 days) were significantly more likely to have IDA (p = 0.002 and p = 0.046, respectively). No statistically significant association was observed with age or gender. Conclusion: This study highlights that more than one-third of children under five years of age in this cohort were affected by iron deficiency anemia, with modifiable factors such as poverty, poor sanitation, and dietary habits playing key roles. Targeted public health interventions focusing on maternal education, improved sanitation, and safer infant feeding practices are urgently needed to reduce the burden of IDA in vulnerable pediatric populations.